Introduction: The Invisible (Migrant) Man. (October 2015) - Charsley, Katharine; Wray, Helena
Migration scholarship has often lagged behind developments in gender studies. The importance of gender has gained increasing recognition, but this has predominantly meant a focus on women migrants. Only recently has a gendered lens been turned to the study of migrant men. Discourses surrounding migration in law and government, and in legal scholarship, remain characterized by neglect or dismissal of the gendered experiences of male migrants. Where they do appear, men are frequently cast as the oppressor of family members or as abusing legal channels of migration. Their vulnerabilities and affective ties and needs are rarely foregrounded. This negative representation may be instrumentalized at a variety of levels, and for a variety of purposes, making it difficult for more nuanced critiques to gain purchase. This special issue seeks to extend the discussion of migration and gender by exploring the ways in which men's gendered experiences of migration remain marginalized.